2022
DOI: 10.5808/gi.22013
|View full text |Cite
|
Sign up to set email alerts
|

In silico genome wide identification and expression analysis of the WUSCHEL-related homeobox gene family in Medicago sativa

Abstract: Alfalfa (Medicago sativa) is an important food and feed crop which rich in mineral sources. The WUSCHEL-related homeobox (WOX) gene family plays important roles in plant development and identification of putative gene families, their structure, and potential functions is a primary step for not only understanding the genetic mechanisms behind various biological process but also for genetic improvement. A variety of computational tools, including MAFFT, HMMER, hidden Markov models, Pfam, SMART, MEGA, ProtTest, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In contrast, genes belonging to different subgroups and clades like BnWOX4/10 (chr13), BnWUS/13B (chr12), and BnWOX9A/9B/14 (chr2) were also located on the same chromosomes. These, however, followed similar patterns with the WOX genes reported in other species like Medicago sativa Triticum aestivum and Hordeum vulgare [17,24].…”
Section: Chromosomal Locationsupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast, genes belonging to different subgroups and clades like BnWOX4/10 (chr13), BnWUS/13B (chr12), and BnWOX9A/9B/14 (chr2) were also located on the same chromosomes. These, however, followed similar patterns with the WOX genes reported in other species like Medicago sativa Triticum aestivum and Hordeum vulgare [17,24].…”
Section: Chromosomal Locationsupporting
confidence: 83%
“…In previous studies, a variable number of WOX genes were reported in different plant species, such as 15 in A. thaliana, 13 in rice, 43 in bread wheat, 34 in Medicago sativa, 10 in Jatropha curcas, and 20 in Hevea brasiliensis [22][23][24][25]. Specific expression of the genes in various organs and cells in plants pointed to their crucial roles in organogenesis [15,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…This gene family is implicated in developmental processes including cell division, development, stem cell repair, organ formation, seed formation, tissues, and organ regeneration [ 83 86 ]. Recent studies have indicated that WOX genes play a role in the regulation of abiotic stress resistance including drought [ 87 ]. In Glycine max, expression of the WOX gene family has been shown to be induced by drought, heat, cold, and salt stress in [ 84 ], and in Arabidopsis, WOX9 was reported to be expressed in the root tip meristem tissue and promote root cell multiplication which is a mechanism of drought tolerance [ 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…This classification is consistent with other reported plants. Even though a previous study identified 34 MsWOXs genes in alfalfa using homeodomain sequences as a query and named them according to their location on the chromosomes [ 54 ], here we identified 14 MsWOXs using comprehensive bioinformatic analysis and named them based on homology to Arabidopsis and Medicago WOX genes (Fig. 1 ), which is helpful to explore novel and established biological functions.…”
Section: Discussionmentioning
confidence: 99%